Adoption in Galatians and Romans : contemporary metaphor theories and the Pauline huiothesia metaphors - Heim, Erin M. (Biblical Interpretation Series, 2017)
In a new study on the Pauline adoption metaphors, Erin Heim applies a wide array of contemporary theories of metaphor in a fresh exegesis of the four instances of adoption ( huiothesia ) metaphors in Galatians and Romans. Though many investigations into biblical metaphors treat only their historical background, Heim argues that the meaning of a metaphor lies in the interanimation of a metaphor and the range of possible backgrounds it draws upon. Using insights from contemporary theories, Heim convincingly demonstrates that the Pauline adoption metaphors are instrumental in shaping the perceptions, emotions, and identity of Paul's first-century audiences.